Functionalization of Wool Fabric Using Pineapple Peel Extract (PPE) as a Natural Dye. Issue 5 (September 2019) - Sheikh, Javed; Agrawal, Ashutosh; Garg, Harsh; Agarwal, Aashi; Mathur, Prasun
Large quantities of pineapple peel waste are discarded every year that can be used for extraction of useful textile functionalization chemicals. In the present work, pineapple peel extract (PPE) was used for simultaneous dyeing and multifunctional finishing of wool fabric. The PPE was used for dyeing wool fabrics, with and without mordants. The dyed fabrics were characterized and evaluated for color values and fastness properties. The functional properties of the dyed fabrics viz. antibacterial activity, UV protection, and antioxidant activity were evaluated. It was confirmed that wool fabric can be dyed using pineapple peel extract without mordants; however, additional color strength can be gained using pre-mordanting. The dyed fabrics showed light shades with good fastness properties along with excellent functional properties.